Multi-functional of TiO2@Ag core–shell nanostructure to prevent hydrogen sulfide formation during anaerobic digestion of sewage sludge with boosting of bio-CH4 production. (1st February 2023) - Hassan, Gamal K.; Mahmoud, Walaa H.; Al-sayed, Aly; Ismail, Sameh H.; El-Sherif, Ahmed A.; Abd El Wahab, S.M.
Highlights: TiO2 @Ag NS has been synthesised and fully characterized. TiO2 @Ag NS enhance the removal of hydrogen sulphide from gas phase of AD. TiO2 @Ag NS can enhance biomethane production from sewage sludge by AD. TiO2 @Ag NS enhance the degradation efficiency of sewage sludge. Abstract: Herein, we report a novel supplement called TiO2 @Ag core–shell nanostructure that revealed a high removal of hydrogen sulfide gas with boosting the bio-methane production from the anaerobic digestion process of sewage sludge. TiO2 @Ag core–shell nanostructure was synthesized by the deposition of Ag shell NPs on TiO2 core NPs using a reduction method. The prepared samples of the core–shell and its components were characterized using different techniques such as XRD, SEM, TEM and AFM. A concentration of TiO2 @Ag core–shell NS (50 mg/L) was supplemented with anaerobic bioreactors to study their effect on the removal of hydrogen sulfide from the anaerobic digestion of sewage sludge compared to silver and titanium dioxide nanoparticles alone. The results showed a 3-fold increase in the produced bio-methane upon the use of TiO2 @Ag core–shell NS with a high removal of hydrogen sulfide (91.9 %) compared to using only silver nanoparticles or titanium dioxide nanoparticles. Concisely, the prepared TiO2 @Ag core–shell NS was multifunctional and more active than its components in removing hydrogen sulfide, enhancing bio-methane production, and detoxifying hazardous materials from sewage sludge.